THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS, WORKLOAD AND EMPLOYEE STATUS ON EMPLOYEE PERFOMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE (STUDY AT THE PEMALI JUANA RIVER BASIN CENTER) - Martikasari Edi Susilastuti; Pahlawansyah Harahap; Wyati Saddewisasi; Ardiani Ika Sulistyawati (ITB AAS Indonesia Surakarta, 2023)
This studies examines the Influence Of Individual Characteristics, Workload and Employee Status On Employee Perfomance With Motivation As An Intervening Variable. In this observe, the population was personnel at the BBWS Pemali Juana office, totaling 329 employees. Based on the studies that has been accomplished, it is able to be concluded that to enhance the performance of BBWS Pemali Juana personnel it is able to be motivated with the aid of individual characteristics, workload and employee repute. Individual traits, workload and worker reputation will affect work motivation and will in the long run enhance employee performance. Furthermore, for the effects of the hypothesis received as follows, character traits have a fine and massive impact. This way that the higher person characteristics will increase employee overall performance. Workload has a wonderful and tremendous effect. This indicates that workload has a fine however not massive impact. With growing workload does now not have an effect on worker overall performance. This is indicated by way of the workload applied so one can have an effect on the performance of each employee although it isn't always dominant. Employment status has a high quality and great effect. So worker repute does not have an effect on employee performance in sporting out their obligations. Individual traits have a tremendous and considerable effect. This approach that man or woman characteristics greatly influence motivation. Employees have excessive motivation at paintings. Workload has a effective and extensive impact on motivation. Employment fame has a positive and extensive impact on motivation. Motivation has a advantageous and sizable effect on worker performance. Keywords: Individual Characteristics, Workload, Employee performance, Motivation, Employee Status